2‐Phenyloxazole‐4‐carboxamide as a Scaffold for Selective Inhibition of Human Monoamine Oxidase B. (7th August 2019) - Di Paolo, Maria L.; Christodoulou, Michael S.; Calogero, Alessandra M.; Pinzi, Luca; Rastelli, Giulio; Passarella, Daniele; Cappelletti, Graziella; Dalla Via, Lisa
Abstract: A series of 2‐phenyloxazoles bearing an amide group at position 4 were designed and synthesized for evaluation as potential inhibitors of human recombinant monoamine oxidases (hrMAOs). Results of kinetics experiments demonstrated that all compounds behave as competitive MAO inhibitors, with good selectivity toward the MAO‐B isoform. The most potent and selective derivatives are characterized by inhibition constant ( K i ) values in the sub‐micromolar range and a good selectivity index ( K i MAO‐A / K i MAO‐B >50). Some derivatives were also found to be able to inhibit MAO activity in nerve growth factor (NGF)‐differentiated PC12 cells, taken as a model of neuronal cells. In particular, 2‐(2‐hydroxyphenyl)‐ N ‐phenyloxazole‐4‐carboxamide (compound4 a ) may be a promising new scaffold, exerting the highest selectivity and inhibitory effect toward MAOs in NGF‐differentiated PC12 cell lysates, without compromising cell viability. Molecular docking analysis allowed a rationalization of the experimentally observed binding affinity and selectivity. Abstract : Most simple, most effective : We assessed the inhibitory behavior of 2‐phenyloxazole‐4‐carboxamide derivatives on monoamine oxidase (MAO) activity. Compound4 a emerged as a potent and selective competitive inhibitor of human recombinant MAO‐B. The significant inhibitory effect on MAO activity in nerve growth factor (NGF)‐differentiated PC12 cells along with an absence of cytotoxicity make4 a a promising new scaffold in drug discovery for neurodegenerative diseases.